Biographical Life Course Research Studying the Biography-History Dynamic - Nilsen, Ann (Springer Nature, 2023)
This open access book explores an approach that connects individual and societal processes throughout history and shifting trends in sociological perspectives, influenced by C. Wright Mills' theories of time and temporality. It traces its origins from American pragmatist thought and Chicago qualitative sociology in the early 20th century to the revival of biographical research in European and American sociology during the 1970s. The book shows empirical studies from this vibrant research approach can bridge methodological gaps between qualitative and quantitative biographical studies, applicable to various topics like class, gender, ethnicity, and intergenerational dimensions.